Nilai Budaya Kerajinan Tikew sebagai Bentuk Kearifan Lokal Tiyuh Gedung Ratu - Solina Solina; Daffa Hibban Bahrisy; Rahmat Prayogi; Bambang Riadi (STIKes Ibnu Sina Ajibarang, 2024)
Indonesia is a country that has rich and diverse culture that has existed since ancient times. Every ethnic group in Indonesia certainly has its own cultural characteristics. Wealth like this is what makes Indonesia famous for its customs, culture, language and literature. With this culture, we as the younger generation should preserve and maintain the authenticity of Indonesian culture. One of them is tikew crafts. Tikew is a form of local culture of the Gedung Ratu community which is made using woven techniques. Tikew is a form of local culture whose existence should be preserved and maintained. This research aims to determine the cultural value of tikew crafts as a form of local wisdom. Efforts to preserve, maintain and develop local culture at Gedung Ratu village officials formed a community of tikew craftsmen as a form of cultural preservation. This research method uses qualitative research methods with interview techniques with one of the Tiyuh Gedung Ratu staff. This research focuses on tikew crafts by examining the cultural values ​​contained therein. As a form of preserving local wisdom in Indonesia.